EVALUATION OF THE ADSORPTION OF THE MODIFIED CARBON BY ULTRASOUND OBTAINED FROM THE MESOCARPIO DE CACAO (Theobroma cacao L.) - Suárez Ramos, Diego (2018)
The present research used cocoa mesocarp (chocolate production residue) as a precursor material of charcoal. This residue was subjected to temperatures of 500°C, 600°C and 700°C for times of 30, 60 and 90 minutes. Charcoals obtained were ground and classified according to their particle diameter in fine and coarse. Subsequently, the adsorption capacity of each treatment with oxalic acid (C2 H2 O4 ) was evaluated to determine the optimum charcoal to be used as a blank. According to results, 600°C60'F treatment showed the best adsorption capacity. This one was subjected to ultrasound at 20kHz at different wave amplitudes (20 % and 40 %) as well as exposure times of 5, 10 and 20 minutes. Evaluation was compared to blank through physicochemical parameters such as chemical kinetics and equilibrium, isotherms of adsorption of C2 H2 O4 , and estimation of the adsorption surface. Finally, results show that exposure to ultrasound generates a positive effect in increasing adsorption capacity of charcoal, obtaining an increase in efficiency of up to 41.84 % and an adsorption surface of 1068.75m2 for treatment C(US)40% 5'.